2006
DOI: 10.1021/es051878z
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cyclopentadienyl Radical from the Gas-Phase Pyrolysis of Hydroquinone, Catechol, and Phenol

Abstract: The formation of radicals from the gas-phase pyrolysis of hydroquinone, catechol, and phenol over a temperature range of 400-750 degrees C was studied using the technique of low-temperature matrix isolation electron paramagnetic resonance (LTMI EPR). Cooling the reactor effluent from pyrolysis in a nitrogen carrier gas to 77 K produces a cryogenic matrix that exhibits poorly resolved EPR spectra. However, using carbon dioxide as a carrier gas formed a matrix that, upon annealing by slowly raising the matrix te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
111
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 59 publications
7
111
0
Order By: Relevance
“…3 Dellinger's group has thoroughly investigated thermal decomposition of CT reporting that both pyrolytic and oxidative decomposition reactions of CT result in the formation of dibenzo-p-dioxin (DD) and dibenzofuran (DF). 2,[5][6][7][8] In one of the contributions of the group, Khachatryan et al, 5 using the technique of low-temperature matrix isolation electron paramagnetic resonance spectroscopy (LTMI-EPR), detected the formation of an o-semiquinone (o-SQ) radical as the most prominent initial intermediate from decomposition of the CT molecule, via fission of one of its phenolic O-H bonds (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…3 Dellinger's group has thoroughly investigated thermal decomposition of CT reporting that both pyrolytic and oxidative decomposition reactions of CT result in the formation of dibenzo-p-dioxin (DD) and dibenzofuran (DF). 2,[5][6][7][8] In one of the contributions of the group, Khachatryan et al, 5 using the technique of low-temperature matrix isolation electron paramagnetic resonance spectroscopy (LTMI-EPR), detected the formation of an o-semiquinone (o-SQ) radical as the most prominent initial intermediate from decomposition of the CT molecule, via fission of one of its phenolic O-H bonds (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore OHCPD is formed but was not persistent enough to acquire its EPR spectrum with the various techniques we used in the previous studies [39,40,42].…”
Section: Temperature Dependence Of Total Radical Accumulationmentioning
confidence: 98%
“…Phenol thermal degradation leads to phenoxy radical by elimination of the hydrogen atom of the hydroxyl group of phenol. Further reaction of phenoxy proceeds by CO elimination to form CPD [39]. In our gasphase phenol thermal degradation study, CPD and phenoxy radicals are, respectively, identified as pyrolysis products and their EPR gas-phase spectra are acquired [39][40][41][42].…”
Section: Time Dependence Of Total Radical Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Nevertheless, HQ and its isomers, catechol (CA; 1,2-dihydroxybenzene) and resorcinol (RE; 1,3-dihydroxybenzene), are harmful to both humans and animals, even at low concentrations, and they are difficult to degrade due to their coexistence and interference during determination. [7][8][9][10] Moreover, they are considered to be environmental pollutants by the United States Environmental Protection Agency (EPA) and the European Union (EU) and banned its use in cosmetics and such formulations.…”
Section: Introductionmentioning
confidence: 99%